2017
DOI: 10.5799/jcei.328744
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Nutritional Status of Hospitalized Cancer Patients

Abstract: In oncology practice, nutrition and also metabolic activity are essential to support the nutritional status and prevent malignant cachexia. It is important to evaluate the patients and plan the maneuvers at the start of the therapy. The primary objective of the study is to define the nutritional status of hospitalized patients and the factors affecting it in order to define the most susceptible patients and maneuvers for better nutritional support. Methods: Patients hospitalized in oncology clinic for therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(29 reference statements)
0
2
0
1
Order By: Relevance
“…Another study carried out in Turkey, reported that younger age was associated with inadequate nutritional status in hospitalised patients with cancer. 33 Among cancer-related variables, we found several variables, including PS, to be significantly associated with nutritional status. A prior study concluded that malnutrition affects PS in patients with pancreatic cancer.…”
Section: Discussionmentioning
confidence: 77%
“…Another study carried out in Turkey, reported that younger age was associated with inadequate nutritional status in hospitalised patients with cancer. 33 Among cancer-related variables, we found several variables, including PS, to be significantly associated with nutritional status. A prior study concluded that malnutrition affects PS in patients with pancreatic cancer.…”
Section: Discussionmentioning
confidence: 77%
“…A relevância dessa relação não diminui na terminalidade de vida, entretanto se intensifica outras sensações causadas pela ausência ou dificuldade de ingestão (Amorim & Silva, 2021)., como por exemplo, que sua sobrevivência está ameaçada, devido à piora da qualidade de vida. Acerca dos sentimentos negativos relacionados com a hospitalização, pode-se correlacionar com um estudo realizado com 423 pacientes internados na especialidade da oncologia, em que os participantes relataram que seu apetite é melhor em casa do que no hospital e a hospitalização impacta na perda de apetite (Ali, Dılşa, Filiz & Güngör, 2017).…”
Section: Discussionunclassified
“…Firstly, the graft preparation is associated with a number of legal and physical issues. Secondly, the preservation of biomechanical and optical functions of the graft and its storage are also problems of high complexity (Costa, Leiva, & Gimenez, 2018;Ito, Terakado, Ichikawa, Zama, Minami, Kudo, & Kanemaki, 2014;Lacerda, Gimenez, Laguna, & Costa, 2017;Maggs, Miller, & Ofri, 2008;Alkan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%